Clinical characterization and etiological insights: a small cohort study of pulmonary infections caused by Microascus spp. in critically ill patients - Zhang, Ting; Cheng, Jian-Jun; Bi, Ru-Ru; Zhu, Jun-Mei; Zhou, Li-Ting; Chen, Yan; Han, Qing-Zhen (Frontiers in Microbiology, 2025)
Microascus spp., globally distributed fungi, are increasingly recognized as causative agents of rare and refractory invasive infections in immunocompromised populations, with approximately 50 cases reported worldwide. This study aimed to characterize the epidemiological features, antifungal resistance profiles, and identification strategies for Microascus-associated pulmonary infections. Ten Microascus isolates were collected from respiratory specimens of patients with pulmonary infections (2021–2024). Clinical characteristics were analyzed, and antifungal susceptibility testing (AFST) was performed following CLSI M38-A3 guidelines. Taxonomic identification integrated MALDI-TOF mass spectrometry, and multilocus phylogenetic analysis (ITS/EF-1α/TUB). Nine of ten cases occurred in hematopoietic stem cell transplant (HSCT) recipients, with concurrent infections by cytomegalovirus (7/9), Pseudomonas aeruginosa (5/9), Corynebacterium striatum (5/9), or Aspergillus spp. (5/9). Three patients succumbed to refractory infections. Morphologically, colonies exhibited olive-to-black concentric rings, floccose hyphae with dark granules, and basally swollen conidiophores producing oval or pear-shaped conidia in chains. Nine isolates were M. gracilis, and one was M. cirrosus. All strains demonstrated resistance to fluconazole, amphotericin B, and flucytosine (MIC >64 μg/mL) but high sensitivity to terbinafine (MIC ≤0.125 μg/mL). MALDI-TOF accurately identified M. gracilis (100%), while M. cirrosus required sequencing for confirmation. Multilocus sequence typing revealed a monophyletic cluster among M. gracilis isolates. Microascus spp. represent underdiagnosed pathogens in HSCT-associated fungal pneumonia, often complicated by polymicrobial infections. Terbinafine demonstrates promising in vitro efficacy against multidrug-resistant strains. A multimodal diagnostic approach combining morphology, MALDI-TOF, and sequencing is essential for species-level identification.